2001
DOI: 10.1038/sj.ejcn.1601236
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and methylmalonic acid levels in pregnant Nepali women. Should cobalamin supplementation be considered?

Abstract: Objective: The aim of this study was to investigate homocysteine and methylmalonic acid levels as markers of functional cobalamin and folate status in pregnant Nepali women. Design: Cross-sectional study. Setting: Patan Hospital, Kathmandu, Nepal. Subjects: A sub-sample (n ¼ 382) of all pregnant women (n ¼ 2856) coming for their first antenatal visit in a 12 month period, 1994 -1995. The selection of the sub-sample was based on maternal haematocrit values, categorised into three groups: severely, moderately an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 36 publications
9
50
0
Order By: Relevance
“…Because a variety of dietary foods are rich in vitamin B 12 and folate, such as fresh fruits and vegetables, which are rich sources of folate (24) , and a nutritional characteristic of ruminant meat, which has high content of vitamin B 12 (25) , (25,26) . Differences of dietary pattern on varieties of area were exemplified, which showed that both folate and vitamin B 12 deficiency were equally prominent in pregnancy (27)(28)(29) . The present study was in accordance with the quite early work by Grainger et al that related vitamin B 12 -deficient diet in pregnant animals to hydrocephalus and other birth defects (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Because a variety of dietary foods are rich in vitamin B 12 and folate, such as fresh fruits and vegetables, which are rich sources of folate (24) , and a nutritional characteristic of ruminant meat, which has high content of vitamin B 12 (25) , (25,26) . Differences of dietary pattern on varieties of area were exemplified, which showed that both folate and vitamin B 12 deficiency were equally prominent in pregnancy (27)(28)(29) . The present study was in accordance with the quite early work by Grainger et al that related vitamin B 12 -deficient diet in pregnant animals to hydrocephalus and other birth defects (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, vitamin B 12 deficiency is quite common and is mainly explained by a diet low in animal products (37) . Two previous studies of pregnant women in Nepal documented that vitamin B 12 deficiency (serum level < 150 pmol/l) was common; 49 % in Kathmandu (38) and 28 % in the Sarlahi District (9) . In our study, the main sources of vitamin B 12 were meat, dairy products and eggs, which were consumed in small amounts by 62 %, 68 % and 25 % of the women, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two prior studies of pregnant Nepali women each found a low prevalence of folate deficiency: 7 % < 4·5 nmol/l (38) and 11 % < 6·7 nmol/l (9) . A study on folate status in Nepali infants found that folate deficiency was nonexistent (39) .…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia was defined by Hb concentration as: mild, ,110 g/l or ,105 g/l for gestational age ,12 weeks or $12 weeks, respectively (20) ; moderate, ,90 to 70 g/l; and severe, ,70 g/l. Micronutrient deficiency was defined with the following cut-offs: Fe deficiency, ferritin ,12 mg/l or TfR .8?5 mg/l; retinol, ,0?70 mmol/l (18) ; a-tocopherol, ,9?3 mmol/l (21) ; vitamin B 12 , ,150 pmol/l (22) ; folate, ,6?7 nmol/l (23) ; and Zn, ,8?6 mmol/l (24) . An additional less conservative cut-off of ,12 mmol/l was also used to define a-tocopherol deficiency (25) .…”
Section: Discussionmentioning
confidence: 99%